Aflatoxins - Occurrence, Detection and Novel Detoxification Strategies 2022
DOI: 10.5772/intechopen.107438
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Occurrence, Detection, and Novel Strategies to Reduce Toxicity in Poultry Species

Abstract: Aflatoxins (AF) are the commonly occurring mycotoxins produced by various Aspergillus species including A. flavus, A. parasiticus, and A. nominus. As secondary metabolites of these fungi, AF may contaminate a variety of food and feedstuffs, especially corn, peanuts, and cottonseed. Among the many known AFs, AFB1 is the most commonly encountered and the most toxic. In poultry, adverse effects of AF include reduction in growth rate and feed efficiency, decreased egg production and hatchability along with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 257 publications
0
3
0
Order By: Relevance
“…The exposure of turkeys to AFB 1 negatively impacts productivity, causing significant economic losses and health problems in the poultry industry because of its toxicity ( 24 ). In an earlier study, a significant decrease in BWG and FCR was observed in poults fed diets with quantities equal to or higher than 400 ppb from 2 to 7 weeks of age ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure of turkeys to AFB 1 negatively impacts productivity, causing significant economic losses and health problems in the poultry industry because of its toxicity ( 24 ). In an earlier study, a significant decrease in BWG and FCR was observed in poults fed diets with quantities equal to or higher than 400 ppb from 2 to 7 weeks of age ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of turkeys to AFB 1 negatively impacts productivity, causing significant economic losses and health problems in the poultry industry because of its toxicity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Along with thermal processing, nonthermal techniques like cold plasma could be used to lower the levels of AFs in some nuts and seeds by as much as 95% . One of the efficient approaches to lower the AF content is the use of non-nutritive adsorbent in toxin contaminated feed to lower the availability of AFs . However, there are many disadvantages to such a technique, including the adsorbent’s insufficient specificity and its high cost.…”
Section: Aflatoxin Detoxification Approachesmentioning
confidence: 99%
“… 73 One of the efficient approaches to lower the AF content is the use of non-nutritive adsorbent in toxin contaminated feed to lower the availability of AFs. 74 However, there are many disadvantages to such a technique, including the adsorbent’s insufficient specificity and its high cost. Their use is also constrained by the accumulation of absorbents in the surroundings due to animal excretion because of their nondegradable property.…”
Section: Aflatoxin Detoxification Approachesmentioning
confidence: 99%